Medium and Large-Scale Farmers and Agricultural Mechanization in Ghana - International Food Policy Research Institute; Savannah Agricultural Research Institute; Council for Scientific and Industrial Research; Ministry of Food and Agriculture, Government of Ghana (International Food Policy Research Institute, 2016)
International Food Policy Research Institute (IFPRI) in collaboration with the Savannah Agricultural Research Institute (SARI) of Council for Scientific and Industrial Research and Ministry of Food and Agriculture designed "Medium and Large-Scale Farmers and Agricultural Mechanization in Ghana" survey targeting large to medium scale farmers and tractor owners. The survey was aimed at characterizing the transition of smallholders farmers who have become medium- and large-scale commercial farmers in Ghana, assessing agricultural machinery ownership, and patterns of demand for agricultural mechanization among farmers in the country. The survey covered a sample of 1843 farm households and contains data on their demography, farming history, land tenure security, farm land use, input use, crop production and tractor ownership among many others. This survey was designed to provide valid estimates at selected district level and not at regional or national level. Estimates generated from the survey data will be case study results for the sampled districts. Farm level and tractor ownership weight variables need to be used when generating these district estimates, otherwise any statistics without weights should be reported as sample statistics. Since small-scale farmers were not the primary focus of this survey, our random sample for this group is likely to have weak statistical power given that the sample was derived from the representative Ghana Agricultural Production Survey (GAPS) sample. Therefore, any comparison by farm size group should be done with caution and would require ex-post statistical power testing for the small-scale farmer's group.